Parametric analysis of the transmission dynamics during indigenous aggregated outbreaks caused by five SARS-CoV-2 strains in Nanjing, China - Ma, Tao; Chen, Cong; Wang, Junjun; Wang, Hengxue; Zhao, Yueyuan; Zhu, Yuanzhao; Yan, Zikang; Ding, Songning; Ding, Jie (Frontiers in Public Health, 2024)
Background SARS-CoV-2 strains have been of great concern due to their high infectivity and antibody evasion. Methods In this study, data were collected on indigenous aggregated outbreaks in Nanjing from January 2020 to December 2022, caused by five strains including the original strain, the Delta variant, and the Omicron variant (BA.2, BA.5.2, and BF.7). The basic epidemiological characteristics of infected individuals were described and then parametric analysis of transmission dynamics was performed, including the calculation of incubation period, serial interval (SI), the basic reproductive number (R0), and the household secondary attack rate (HSAR). Finally, we compared the trends of transmission dynamic parameters of different strains. Results The incubation period for the original strain, the Delta variant, Omicron BA.2, Omicron BA.5.2, and Omicron BF.7 were 6 d (95% CI: 3.5–7.5 d), 5 d (95% CI: 4.0–6.0 d), 3 d (95% CI: 3.0–4.0 d), 3 d (95% CI: 3.0–3.0 d), and 2 d (95% CI: 2.0–3.0 d), respectively; Also, the SI of the five strains were 5.69 d, 4.79 d, 2.7 d, 2.12 d, and 2.43 d, respectively. Notably, the incubation period and SI of the five had both a progressive shortening trend (p < 0.001); Moreover, R0 of the five were 2.39 (95% CI: 1.30–4.29), 3.73 (95% CI: 2.66–5.15), 5.28 (95% CI: 3.52–8.10), 5.54 (95% CI: 2.69–11.17), 7.39 (95% CI: 2.97–18.76), with an increasing trend gradually (p < 0.01); HSAR of the five were 25.5% (95% CI: 20.1–31.7%), 27.4% (95% CI: 22.0–33.4%), 42.9% (95% CI: 34.3–51.8%), 53.1% (95% CI: 45.0–60.9%), 41.4% (95% CI, 25.5–59.3%), also with an increasing trend (p < 0.001). Conclusion Compared to the original strain, the incubation period and SI decreased while R0 and HSAR increased, suggesting that transmission in the population was faster and the scope of the population was wider. Overall, it’s crucial to keep implementing comprehensive measures like monitoring and alert systems, herd immunization plans, and outbreak control.